Effects of climatic stress on the severity of pneumonia and reproductive functions of local crossbred does infected by Mannheimia haemolytica - Maqbool, Arsalan (2020)
Pneumonic mannheimiosis is a respiratory disease which has been considered a major constraint to the development of small ruminant production. This disease is characterized by acute febrile course with severe fibrinopurulent bronchopneumonia and septicaemia occurring with a higher prevalence in goats. The main causative agent is Mannheimia haemolytica serotype A2, which is the most frequent isolate from pneumonic lungs. It is a commensal of the nasopharynx and is an opportunist organism that gains access to the lungs when the host is immunocompromised. To the best of our knowledge, the effects of climatic stress on the severity of pneumonia and changes in femalereproductive physiology due to M. haemolytica A2 infection have not yet been reported. Therefore, this research has been designed to evaluate the effects of climatic stress on the severity of pneumonia and reproductive physiology in experimental does challenged with M. haemolytica serotype A2 in the rainy and hot seasons. A total of twenty-four female goats were divided equally for the rainy and hot season over the period of 60 days each. For each season, 12 goats were divided into three treatment groups i.e. negative control (group 1), non-vaccinated (group 2), and vaccinated (group 3). All goats were acclimatized and synchronized before experimental trials. At week 1, group 3 were immunized with a commercially available vaccine, while group 2 and group 1 were given phosphate buffer saline (PBS). Groups 2 and group 3 were intranasally challenged with M. haemolytica A2 with 105 cfu/ml 14 days post-vaccination, whereas goats in group 1 were inoculated intranasally with PBS. Experimental animals were observed for clinical responses throughout the study period. Blood samples were collected weekly for the determination of immune responses (haptoglobin, serum amyloid A, interleukin-1β, interleukin-6, immunoglobulins-M, immunoglobulins-G, cortisol and heat shock protein-70), and reproductive hormones (progesterone, estrogen, follicle-stimulating hormone, luteinizing hormone). At the end of the study period, all animals were euthanized for post mortem and histopathological examination. Environmental temperature and humidity were also recorded throughout the study. The present study revealed that the environmental temperature showed non-significant (p>0.05) difference between the rainy and hot season, while its relative humidity was significantly (p<0.05) higher during the rainy season compared the hot season. The findings of the present study demonstrated that the does inoculated with M. haemolytica A2 had significantly (p<0.05) increased rectal temperature, heart and respiratory rate after twenty-four hours post-challenge in group 2 compared to group 1 and group 3 in both seasons. The mean weekly lung auscultation scores of group 2 goats were significantly higher (p<0.05) in the rainy season compared to those in the hot season. A significant (p<0.05) decline in the body condition score was observed in group 2 goats in the rainy season compared to those in the hot season. The present study revealed a significant (p<0.05) increased concentrations of immune parameters in group 2 compared to group 1 and 3 in both seasons. The magnitude of interleukin-1β, cortisol and heat shock protein-70 were significantly (p<0.05) increased in group 2 in the rainy compared to that in the hot season. While, the acute phase proteins and interleukin-6 responses were similar within each group in both seasons. The IgM response significantly (p<0.05) increased post-vaccination in group 3, which further increased significantly (p<0.05) post-challenge and remained higher until week 5, followed by significant (p<0.05) increase in IgG levels and remained increased throughout the study in both seasons. The present study revealed a significant (p<0.05) increase in progesterone concentrations of group 2 post-challenge. Besides, estrogen, follicle-stimulating hormone and luteinizing hormone concentrations significantly (p<0.05) decreased in group 2 compared to group 1 and group 3 in both seasons. The significant (p<0.05) histopathological changes were observed in group 2 compared to group 1 and 3 in both seasons; these changes were characterized by congestion, degeneration, and necrosis of epithelial cells with moderate to severe inflammatory cell infiltration in lungs, submandibular lymph nodes, reproductive organs (ovaries, uterus, cervix), anterior pituitary glands, mammary glands and supra-mammary lymph nodes. In conclusion, climatic stress has an effect on the severity of pneumonia; the intensity of infection due to M. haemolytica A2 is higher in the rainy season compared to the hot season. M. haemolytica A2 infection has an association with the reproductive physiology of does under tropical conditions. Furthermore, it is observed that vaccination provided defensive shelter against mannheimiosis.